Effects of short-term self-selected resistance training on anxiety and depression scores of sedentary individuals (Research, Society and Development, 2020)
A positive affective experience, making exercise more pleasurable, less stressful, achieving greater satisfaction and intrinsic motivation experience through resistance training may be accomplished by performing self-selected exercises. These exercises can also lead to other health-related and performance outcomes. Thus, this study aimed to analyze the effects of a short-term self-selected resistance training on levels of anxiety and depression in sedentary individuals. Twenty-one individuals, aged between 20 and 50 years, were assigned to Training Group (TG) and Control Group (CG). The TG underwent 4 weeks of resistance training, 2 sessions per week, with self-selected intensities. Anxiety and depression scores were collected before and after intervention using the Hospital Anxiety and Depression Scale (HAD). The results showed that the TG presented a significant reduction in anxiety scores (8.9±2.0 to 7.1±2.1; p=0.008) with a large effect size (d=0.71). Depression scores showed no significant difference after intervention (6.3±2.6 to 5.4±2.6; p=0.094), with a small effect size (d=0.346). The CG showed slight non-significant increase in depression scores (6.3±3.1 to 6.8±3.7; p=0.297), with small effect size (d= 0.146). In conclusion, resistance training with self-selected intensity reduced anxiety scores and kept depression scores in a healthy level in sedentary individuals.